Values, preferences and burden of treatment for the initiation of GLP-1 receptor agonists and SGLT-2 inhibitors in adult patients with type 2 diabetes: a systematic review - González González, José Gerardo; Díaz González Colmenero, Alejandro; Millán Alanís, Juan Manuel; Lytvyn, Lyubov; Solís, Ricardo Cesar; Mustafa, Reem A; Palmer, Suetonia C; Li, Sheyu; Hao, Qiukui; Alvarez Villalobos, Neri Alejandro; Vandvik, Per Olav; Rodríguez Gutiérrez, René
Objectives Assess values, preferences and burden of treatment that patients with type 2 diabetes consider when initiating glucagon-like peptide-1 receptor agonists (GLP-1 RA) or sodium-glucose cotransporter-2 inhibitors (SGLT-2i) compared with other glucose-lowering options.Methods Paired reviewers independently included studies reporting quantitative or qualitative methods to assess values, preferences and burden of treatment reported by patients with type 2 diabetes regarding the initiation of GLP-1 RA or SGLT-2i over other alternatives. A systematic search in MEDLINE, Scopus, EMBASE, Web of Science and Cochrane Central Register of Controlled Trials from inception until May 2020 was performed by an experienced librarian. Risk of bias was assessed with a specifically designed tool for values and preferences studies.Results 17 studies (7296 patients) proved eligible. Studies fulfilling criteria for SGLT-2i were not identified. Five studies (2662 patients) evaluated preferences for GLP-1 RA compared with other glucose-lowering medications. 12 studies (4634 patients) evaluated preferences between, at least, two kinds of GLP-1 RA or their injection devices based on the following attributes: efficacy, dose, application frequency, device characteristics. Among studies comparing GLP-1 RA to other glucose-lowering medications, some preferences were observed for dypeptil peptidase-4 inhibitors compared with once daily liraglutide. Comparing different attributes of GLP-1 RA drugs and devices, cardiovascular risk reduction, glucose lowering potential, once weekly and simple administered regimens were the most preferred.Conclusions As no evidence for preferences on SGLT-2i was available, only preferences for GLP-1 RA were assessed; however, evidence is still limited for the latter. Studies comparing preferences for GLP1-RA to other glucose-lowering alternatives only included twice daily or once daily injection regimens of GLP-1 RA drugs. According to our findings, once weekly alternatives are widely preferred than the formers. The extent to which patients with type 2 diabetes value reduced adverse cardiovascular and kidney outcomes, weighed benefits against harms and burden of treatment is limited and with very low certainty.